Hukum Yang Mengatur Tentang Kesetaraan Hak Para Penyandang Disabilitas di Masyarakat Luas: Bagaimana Implementasinya? - Alief Addzakir; Dhivaa Azka Ismaila Putri Djaelani; Rikku Rahma Ayu Prawira; Saomy Dian Supratman; Maulia Depriya Kembara (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The implementation of equal rights for persons with disabilities in Indonesia still needs to be improved. This is a challenge for us as Indonesian citizens to realize equal rights, especially for persons with disabilities. This article was prepared to explore the public's knowledge of persons with disabilities, including the rights that they must obtain. This article was also compiled with the hope of increasing public awareness of the importance of equal rights for persons with disabilities. The researcher used a qualitative method with a survey approach to the wider community, which targeted students at SMAN 25 Bandung. Researchers conducted socialization activities and discussions to find out how the wider community's knowledge about people with disabilities, and the urgency of accessibility for them because this is also one of the processes to implement these laws. It was found that the community already knows what people with disabilities are but there is still a stigma that arises against them. In the environment, there are still many people who feel reluctant or even afraid when facing people with disabilities, so the process of implementing equal rights for them is hampered. Therefore, it is important to give people an understanding of how crucial equal rights are for people with disabilities. They do not need to be fixed or cured, they just need to be accepted for who they are and not treated differently from the rest of society.